Chronic Undernutrition Differentially Changes Muscle Fiber Types Organization and Distribution in the EDL Muscle Fascicles - Rodriguez-Torres, Erika E.; Viveros-Rogel, Jorge; López-García, Kenia; Vázquez-Mendoza, Enrique; Chávez-Fragoso, Gonzalo; Quiroz-González, Salvador; Jiménez-Estrada, Ismael (Frontiers in Physiology, 2020)
Fiber type composition, organization, and distribution are key elements in muscle functioning. These properties can be modified by intrinsic and/or extrinsic factors. Currently, there is no methodology to quantitatively analyze such modifications. First, we propose a fractal approach to determine fiber type organization, using the software Fractalyse. Secondly, we applied the kernel methodology from machine learning to build radial-basis functions for the spatial distribution of fibers, by dividing into square cells a two-dimensional binary image for the spatial distribution of fibers from a muscle fascicle and mounting on each cell a radial basis function in such a way that the sum of all cell functions creates a smooth version of the fiber histogram on the cell grid. The distribution functions thus created belong in a reproducing kernel Hilbert space which permits us to regard them as vectors and measure distances and angles between them. In this study, we analyzed fiber types organization and distribution in fascicles (F2, F3, F4, and F5) of the extensor digitorum longus muscle (EDLm) from control and undernourished male rats. Fibers were classified according to the ATPase activity in slow, intermediate and fast. Then, the (x, y) coordinates of fibers were used to build binary images and distribution functions for each fiber type. The fractal organization analysis showed that fast and intermediate fibers, from both groups, had a fractal organization within the four fascicles (i.e., the fiber assembly is distributed in clusters). We also showed that chronic undernutrition altered the organization of fast fibers in the F3, although it still is considered a fractal organization. Distribution function analysis showed that each fiber type (slow, intermediate, and fast) has a unique distribution within the fascicles, in both conditions. However, chronic undernutrition modified the intra-fascicular fiber types distributions, except in the F2. Altogether, these results showed that the methodology herein proposed allows quantitative analysis of changes in the organization and distribution of fiber types. Furthermore, we showed that chronic undernutrition changed not only the fiber type composition but also the organization and distribution, which could affect the muscle functioning and ultimately, the behavior (e.g., locomotion).